"Are you ready?" Validation of the Hospital Change Readiness (HCR) Questionnaire. Issue 8 (26th August 2020) - Pomare, Chiara; Ellis, Louise A; Long, Janet C; Churruca, Kate; Tran, Yvonne; Braithwaite, Jeffrey
Abstract : Objective: Organisational change in hospitals is a frequent, seemingly inevitable occurrence. A critical precursor to successful organisational change is change readiness. This paper presents the adaptation of a self-report measure of change readiness for hospital staff, examines its reliability and validity, and evaluates the relationship between hospital change readiness (HCR) and staff well-being. Methods: The questionnaire was piloted among 153 staff from a large metropolitan, public hospital in Sydney, Australia. The hospital was undergoing a major change involving a multimillion-dollar development project that included a new building and new models of care. Construct validity was evaluated by confirmatory factor analysis (CFA) and reliability was assessed by internal consistency. Differences between professional groups were examined using regression analyses and structural equation modelling (SEM) was used to test the relationship between change readiness and staff well-being (job satisfaction and burnout). Results: The HCR Questionnaire was found to reflect theoretically derived and empirically observed domains and have high internal reliability. CFA identified that a two-factor structure demonstrated excellent fit. Cronbach's alpha for the two subscales (appropriateness and change efficacy) was 0.85 and 0.75, respectively. No statistically significant differences of HCR were identified between professional groups. SEM revealed that perceiving change as appropriate was significantly positively related to job satisfaction (0.33) and significantly negatively related to burnout (−0.30), and feeling capable in implementing the change was significantly negatively related to burnout (−0.40). Conclusions: The HCR Questionnaire provides reliable information on how prepared hospital staff felt for organisational change and showed significant relationships with staff well-being. This questionnaire is validated for the Australian hospital context, particularly in the case of hospital redevelopment. It can be used to help manage times of hospital organisational change with minimal disruption to the quality and safety of patient care.